Uso de animais pelas populações tradicionais: um panorama da Etnozoologia no Brasil - Santos, Suellen da Silva (2023)
Human beings relate to different animal species in different ways. These interactions are evidenced in ethnozoological studies, which seek to understand the knowledge and uses attributed to the species, perform hypotheses testing and thus provide data that can serve as a subsidy in management and conservation plans. In this sense, this thesis was structured in the compilation of data on the utilitarian attributions destined to wild fauna species, being structured through a theoretical foundation and two articles. The first paper is a case study that objective was to record the knowledge and use of the avifauna in the municipality of Congo, present in the state of Paraíba, Northeastern Brazil. Fifty people were interviewed (22 men and 28 women), men cite a greater number of species when compared to women. 68 birds were identified, distributed in 20 orders, 34 families and 62 genera, distinguished by the number of species and citations of use: Columbidae, Thraupidae, Cuculidae and Psittacidae. The species are used for food, captive breeding and medicinal purposes, where the food category has gained greater local importance. Categories related to people's perception of the behavior of some species were also recorded, namely: control and bioindication. Regarding the utility value of the species, the analyzes carried out for the use values showed a positive correlation between VUgeneral and VUcurrent, VUgeneral and VUpotential, and VUcurrent and VUpotential, showing that the best-known species tend to be the most used in the study location. The second paper the objective was to evaluate the current panorama of ethnozoological publications developed in Brazil, highlighting trends in use aimed at zoological classes. The search for articles was carried out through the Web of Science and Scopus databases, evaluating 85 papers, developed between 1999 and 2022. The main theme addressed is related to studies in specialized ethnozoology, focusing on a particular zoological group or species. These studies prevailed in gradual growth over the last few years, where the Northeast region and the Caatinga biome are highlighted. A total of 829 species were identified, including 270 birds, 229 fish, 102 reptiles, 86 mammals, 58 insects, 27 molluscs, 25 crustaceans, 13 amphibians, 9 echinoderms, 7 arachnids, 1 annelid, 1 cnidarian and 1 centipede. There was a greater representation of issues addressed in the food and medicinal category. Among the zoological groups felt, the vertebrates stand out. Spearman's correlation showed a positive result between the sum of uses and the number of studies. The Kruskal-Wallis test revealed that the zoological classes, asteroid, bivalve, chilopoda, echinoidea and hydrozoa are below average in number of studies and associations of uses. These data indicate that some classes and faunal groups XI present greater intensity of assessments, requiring greater investment. Others due to the utilitarian importance of certain species are presented with greater emphasis. Thus, evaluations with greater scientific rigor are needed to identify the species that may come under pressure from use, in addition to understanding the sociocultural aspects that lead to these attitudes. In order to delimit, when necessary, conservation strategies aimed at certain biological resources, considering the cultural issues established for a population. This scientific investment tends to have a considerable impact on the consolidation of ethnozoology as a science worldwide, keeping Brazil in the spotlight in carrying out such research.